Effect of exercise training on nitric oxide and nitrate/nitrite (NOx) production: A systematic review and meta-analysis - Arefirad, Tahereh; Seif, Ehsan; Sepidarkish, Mahdi; Mohammadian Khonsari, Nami; Mousavifar, Seyedeh Azam; Yazdani, Shahrooz; Rahimi, Fatemeh; Einollahi, Faezeh; Heshmati, Javad; Qorbani, Mostafa (Frontiers in Physiology, 2022)
Background: Exercise and physical activity can improve circulation through various mechanisms such as the increment of nitric oxide (NO) production by affecting vascular endothelial nitric oxide synthase and reducing reactive oxygen species (ROS). Although theoretically, this mechanism is well known, in living subjects, studies found controversies regarding the association of NO production and its metabolites (nitrate/nitrite (NOx)) and physical activity. Hence, this systematic review and meta-analysis was designed to gather all these studies and evaluate the effects of exercise training, physical activity duration, and length on the mean change of serum/plasma NO and NOx. Method: We searched all available bibliographic electronic databases from inception through May 2022 to include all randomized controlled trials (RCT) and quasi-experimental trials which assessed the effect of exercise and training on the NO and NOx level. Random-effects meta-analysis method was used to pool the standardized mean difference (SMD) and 95% confidence interval (CI) of included RCT studies which assessed the effect of training. Stratified meta-analysis was performed according to the type of exercise (high-intensity interval training (HIIT), aerobic training (AT), the duration of exercise (≤8 and > 8 weeks), and length of exercise in each session ≥40 and 40 < minutes) Results: Overall, fifteen and ten studies were included in the systematic review and meta-analysis, respectively. According to the random-effects meta-analysis, exercise significantly increased the mean change of NO and NOx compared to control (SMD: 1.82 95%CI: 1.14 to 2.49. In the stratified meta-analysis, the mean change of NO and NOx in the intervention group was significantly higher than in the control group in the AT (SMD:1.36 95%CI: 0.55 to 2.18), HIIT (SMD:2.55 95%CI: 1.14 to 3.96), duration of ≤8 (SMD:2.29 95%CI: 1.24 to 3.35) and > 8 weeks (SMD:1.19 95%CI: 0.52 to 1.86), length of ≥40 (SMD:1.61 95%CI: 1.04 to 2.18) and 40 < minutes in each session (SMD:2.07 95%CI: 0.79 to 3.35). Conclusion: The findings of this study indicate that regardless of exercise duration, length